2006
DOI: 10.1097/00001756-200604240-00007
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of the number???size interference task in children

Abstract: In this functional magnetic resonance imaging study, 17 children were asked to make numerical and physical magnitude classifications while ignoring the other stimulus dimension (number-size interference task). Digit pairs were either incongruent (3 8) or neutral (3 8). Generally, numerical magnitude interferes with font size (congruity effect). Moreover, relative to numerically adjacent digits far ones yield quicker responses (distance effect). Behaviourally, robust distance and congruity effects were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 18 publications
7
78
1
Order By: Relevance
“…In addition, functional imaging studies in humans show that the frontal lobe represents aspects of nonverbal quantity representations even in the absence of task demands (37). Interestingly, quantity activation in the frontal lobe is particularly prominent in children (38,39). Future single-cell studies are needed to clarify whether complex quantity judgements require an interplay with, or readout by, more executive structures, such as the prefrontal cortex (36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, functional imaging studies in humans show that the frontal lobe represents aspects of nonverbal quantity representations even in the absence of task demands (37). Interestingly, quantity activation in the frontal lobe is particularly prominent in children (38,39). Future single-cell studies are needed to clarify whether complex quantity judgements require an interplay with, or readout by, more executive structures, such as the prefrontal cortex (36).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pediatric neuroimaging studies showed that young children recruited the prefrontal cortex more than adults during number discrimination tasks. In contrast, intraparietal sulcus activation during number comparison increased across development Kaufmann et al, 2006). Researchers suggested that this frontal to parietal shift from childhood to adulthood may reflect a decrease in the need for domain general cognitive resources such as working memory and attention as children begin to process number symbols automatically (Cantlon et al, 2009a(Cantlon et al, , 2006Venkatraman et al, 2005).…”
Section: Frontal Vs Parietalmentioning
confidence: 99%
“…The frontal cortex has been identified as important for number processing in single-cell recordings from neurons in non-human primates (Andreas Nieder et al, 2002). Additionally, developmental imaging studies have documented that brain activation during numerical processing shifts from the frontal cortex to the parietal cortex across development Cantlon et al, 2006;Kaufmann et al, 2006). A quantitative meta-analysis that synthesized studies examining brain regions that are correlated with basic number processing and calculation tasks in adults further supported the idea that the frontal cortex is important for number processing in adults (Arsalidou and Taylor, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation was that the proposed models of number processing did not lead us to anticipate any valuable difference at anterior sites. Nevertheless, a number of studies have already suggested that the involvement of the prefrontal regions in number comparison (Ansari, Garcia, Lucas, Hamon, & Dhital, 2005;Kaufmann et al, 2006;Pinel et al, 2001). More importantly, earlier ERP studies of face processing showed a large and consistent positive wave between 140 and 200 ms over frontal midline sites.…”
Section: Introductionmentioning
confidence: 99%